Puzzling Situation of Acetaminophen Toxicity in a Referral Hospital, Tehran, Iran: Acetaminophen toxicity in a referral hospital - Pajoumand, Abdolkarim; Talaie, Haleh; Alinia, Tahereh; Mahdavinejad, Arezoo (Iranian Journal of Pharmaceutical Sciences, 2018)
Acetaminophen carries a higher risk of overdose. A puzzling situation of acetaminophen toxicity was encouraging enough to explore the epidemiologic situation of acetaminophen toxicity and its outcomes among patients acquired poisoning. This cross-sectional study retrospectively reviewed the medical records of 185 patients with acetaminophen poisoning referred to Loghman Hakim Hospital. Toxicity determined by acetaminophen serum concentration and time elapsed after drug ingestion. Demographics, laboratory markers, toxic hepatitis, renal failures, and liver enzyme elevations were compared between toxic and non-toxic patients. Twelve cases belonged to the former group and 173 patients fitted with the latter one. Having a mean age of 24.27±7.19 and 21.58±3.47 years, respectively, females were predominant. The average serum acetaminophen level was 70.37±61.92 and 24.90±26.36 within toxic and nontoxic patients, respectively. Median of consumed tablets were estimated as 40 for non-toxic and 18 for toxic patients (p=0.017). Mean hospital stay was 1.75±1.05 days for toxic patients and 1.35±3.25 days for the non-toxic group (p-value<0.001), and of whom 92.4 % were discharged within the first day. The laboratory assessments revealed no significant difference between groups. No death was recorded. Whereas hepatotoxicity was present in three toxic patients, renal failure was predominant in non-toxic patients. Rarely, a rise in liver enzyme was noticed; however, 33.33 % of toxic and 2.31 % of the non-toxic group had elevated AST; and 33.33 % of toxic versus 1.73 % percent of non-toxic patients had increased ALT. Acetaminophen toxicity is a worldwide noteworthy cause of poisoning which has distinct mortality and morbidity rates and showed an amazing and undebatable poisoning effect in the present study. A comprehensive study is required to examine the possible reasons for the difference between Iranian acetaminophen products with other non-Iranian company products.